Generation of beta-amyloid in the secretory pathway in neuronal and nonneuronal cells. - Busciglio, J (1993)
The cellular mechanism underlying the generation of beta-amyloid in Alzheimer disease and its relationship to the normal metabolism of the amyloid precursor protein are unknown. In this report, we show that 3- and 4-kDa peptides derived from amyloid precursor protein are normally secreted. Epitope mapping and radiolabel sequence analysis suggest that the 4-kDa peptide is closely related to full-length beta-amyloid and the 3-kDa species is a heterogeneous set of peptides truncated at the beta-amyloid N terminus. The beta-amyloid peptides are secreted in parallel with amyloid precursor protein. Inhibitors of Golgi processing inhibit secretion of beta-amyloid peptides, whereas lysosomal inhibitors have no effect. The secretion of beta-amyloid-related peptides occurs in a wide variety of cell types, but which peptides are produced and their absolute levels are dependent on cell type. Human astrocytes generated higher levels of beta-amyloid than any other cell type examined. These results suggest that beta-amyloid is generated in the secretory pathway and provide evidence that glial cells are a major source of beta-amyloid production in the brain.